1953
DOI: 10.1192/bjp.99.415.291
|View full text |Cite
|
Sign up to set email alerts
|

The High Incidence of Huntington's Chorea in the Duchy of Cornwall

Abstract: When one finds a legend associated with a disease it may be accepted as a general rule that little is known about its true cause. This is exemplified by Huntington's chorea, of which it is said that the original case was a man who imitated Christ's agony on the Cross. A great deal of work has been done on this complaint, but much of it has been to do no more than to confirm the findings of Abel Huntington, who recognized its hereditary nature in 1797.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1954
1954
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In the present study, patients meeting DSM-III criteria for schizophrenia were rarely seen. Apart from ourselves, only Davenport (1916), Dewhurst et al (1969) and Bickford & Ellison (1953) have reported major affective disorder as the most common psychosis in HD. There are three possible reasons for this variation in reporting.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, patients meeting DSM-III criteria for schizophrenia were rarely seen. Apart from ourselves, only Davenport (1916), Dewhurst et al (1969) and Bickford & Ellison (1953) have reported major affective disorder as the most common psychosis in HD. There are three possible reasons for this variation in reporting.…”
Section: Discussionmentioning
confidence: 94%
“…Bickford and Ellison (1953) obtained a higher figure amongst only those Cornish families who had a member in the mental hospital, so that the true incidence of the disease in that county is likely to be considerably greater. This, however, is probably related to the limited movements of the population in Cornwall on account of its isolated geographical position.…”
Section: Pedigree Eightmentioning
confidence: 92%
“…Bickford and Ellison (1953) have observed a high incidence of suicide in their series in Cornwall and give this as a reason for some of their cases receiving awards for gallantry during the war. The fishermen of North-East Scotland have long had a reputation for skill, endurance, and courage.…”
Section: Analysis Of Clinical Detailsmentioning
confidence: 94%
“…A comparatively rare disease which runs in families should be found more frequently in some areas than in others, and, in fact, localized collections of cases of Huntington's chorea have been described in Cornwall and Northampton by Bickford and Ellison (1953) and Pleydell (1954) respectively.…”
Section: Summaymentioning
confidence: 99%